2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610695
|View full text |Cite
|
Sign up to set email alerts
|

Shape matching by integral invariants on eccentricity transformed images

Abstract: ² Matching occluded and noisy shapes is a frequently encountered problem in vision and medical image analysis and more generally in computer vision. To keep track of changes inside breast, it is important for a computer aided diagnosis system (CAD) to establish correspondences between regions of interest. Shape transformations, computed both with integral invariants and geodesic distance yield signatures that are invariant to isometric deformations, such as bending and articulations. Integral invariants are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Contour flexibility [23] makes effort to represent the deformable potential at each point along the contour and shows that both local and global features can be extracted by this descriptor. There are also other similar methods in [24], [25], [35], [43].…”
Section: Related Workmentioning
confidence: 99%
“…Contour flexibility [23] makes effort to represent the deformable potential at each point along the contour and shows that both local and global features can be extracted by this descriptor. There are also other similar methods in [24], [25], [35], [43].…”
Section: Related Workmentioning
confidence: 99%
“…[18] Other studies [60,61] confirmed its efficiency in matching visual parts and shape contexts. However, the method suffers from the "city block" problem and sub-pixel accuracy, which has subsequently been improved [62] using the Fast Marching Algorithm. [63][64][65] Other effective methods to match shapes include: Eccentricity transforms, [35,[66][67][68] Skeletonization, [69,70] dynamic programing, [32] Fast Sweeping Algorithm, [71,72] Ant Colony Optimization, [73] Bee Colony optimization, [74][75][76] and Bending invariants.…”
Section: Approaches To Match Shapesmentioning
confidence: 99%